A blind robust color image watermarking method based on discrete wavelet transform and discrete cosine transform using grayscale watermark image. (10th February 2022) - Gul, Ertugrul
Abstract: With the rapid development of internet technology, digital images are easily accessed and tampered by unauthorized users. Therefore, copyright of color images has become an important challenge in nowadays. Robust color image watermarking methods have emerged to provide copyright. However, robust watermarking methods must satisfy the requirements such as robustness, imperceptibility, capacity, and security. Therefore, researchers are focused on methods using grayscale watermark instead of the binary watermark to increase capacity. Grayscale watermark based robust color image watermarking methods are mostly semi‐blind and non‐blind. However, these methods have limited utilization areas since the original image, original watermark, or side information is required. To address these drawbacks, we propose a blind robust color image watermarking method using grayscale watermark. In the proposed watermark embedding procedure, one‐level discrete wavelet transform is performed on the Cb color component. Then, scrambled watermark pixels are hidden into coefficients of 4 × 4 discrete cosine transform (DCT) matrices of LL subband by using dividing‐based new watermark embedding formula. In the watermark extracting procedure, watermark pixels are extracted from coefficients of DCT matrices by using dividing‐based extracting formula. The performance is demonstrated against various attacks and experimental results indicate that the presented method ensures robustness while preserving imperceptibility.